The Effects of Self-Regulation by Clinial Information Program to Glycemic Control Behaviors Score and Glycosyted Hemoglobin Level on Uncontrolled Type 2 Diabetes - Baiphimai, Juthamas; Leelukkanaveera, Yuwadee; Srisuriyawet, Rungrat (Journal of Public Health Nursing, 2017)
Achieving the control of blood sugar levels among diabetic patients remains an urgent problem that needs addressing to reduce diabetic complications and improve their quality of life. This quasi-experimental research aimed to examine the effects of a self-regulation intervention by clinical information program to improve glycemic control behaviors score and glycosyted hemoglobin levels (HbA1C) among uncontrolled type 2 diabetic patients. The study sample was patients from Pak Thong Chai district they had been diagnosed with uncontrolled type-2 diabetes by a physician and HbA1c >7 %, they were allocated by sub-districts health promotion hospital, there were highest uncontrolled diabetes. There were randomly selected to be the experimental and comparison groups. Twenty-six subjects from Muangpak Sub-district Health Promotion Hospital were assigned to be in the experimental group. Twenty-four subjects from Takhob Sub-district Health Promotion Hospital were selected for the comparison group. Only the experimental group received the self-regulation intervention through a clinical information program for 18 weeks. The comparison group received the usual care at their HPH. Glycemic control behaviors and HbA1C of diabetic patients were measured before and after the intervention. Data were analyzed by Chi-square and independent t-test. Results founded the effect of a self-regulation intervention by clinical information program had statistic significantly increased the mean glycemic control behaviors score and statistic significantly decreased the mean HbA1C level at experimental purpose versus the comparison group by p < .05. Findings of this study suggests that the self-regulation by clinical information program is an effective intervention to improve glycemic control behaviors and reduce glycosyted hemoglobin level. So health care providers should implicate this intervention to primary health care for uncontrolled type 2 diabetes.